A Study of Some Biochemical Changes in Hydatid Cyst Patients Before And After Surgical removal of hydatid cyst - B. K., Sura (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2013)
Hydatid disease is a major public health and economic problem in Iraq causing morbidity and mortality, This study was done to illustrate some biochemical changes, hemoglobin, blood group and CRP in hydatid cyst patients before and after 15 days of surgery. Twenty patients with hydatid liver cyst infection were enrolled in this study consist of (15 male) and (5 female), Those patients were matched with twenty (14 male) and (6 female) apparently healthy subjects as controls, The results of the study were as the following Significantly high serum triglyceride and serum bilirubin levels were observed in patients with hydatid cyst before and after 15 days of surgical removal when compared with healthy controls And significantly high serum bilirubin level in hydatid cyst patients before surgery when compared with patients after 15 days of surgical removal of the cyst. Blood glucose, urea and hemoglobin level for both studied subjects were within normal range as in healthy controls. Group O was more frequently in hydatid cyst patients than non O group (A, B, AB), Elevated CRP in 14% of hydatid cyst patients before surgery when compared with healthy controls, while after 15 days of surgical removal the mean level of CRP was decreased to 4% . In conclusion all studied parameters may be helpful in following up the effectiveness of surgical treatment. Further investigation in this regard with a larger group of patients is recommended to explore the potential of these parameters compared to alternative measures in monitoring hydatidosis infection and surgical removal of hydatid cyst on hydatid cyst patients.